Relationship of academic courses and clinical internships to performance on the National Qualified Examination for Registered Professional Nurses (NQEX-RPN) - Huimin Xiao; Weiwei Wu; Yan Lin; Xuan Zhang (Elsevier, 2014)
Background: Success in the National Qualified Examination for Registered Professional Nurses (NQEX-RPN) is a critical issue for each nursing student and every nursing school. However, to date, little research has been conducted regarding the degree of risk for licensure failure associated with specific academic courses and clinical internships in Mainland China. Objective: This study aimed to explore the relationship of academic courses and clinical internships to performance on the NQEX-RPN in Mainland China. Methods: This was a retrospective descriptive study. Two hundred twenty-eight new graduates were recruited from a four-year baccalaureate nursing program in Mainland China. The scores of academic courses and clinical internships were recorded from the Teaching and Learning administration of the university. The NQEX-RPN performance data was collected from the Provincial Health Department. Personal information was collected from the participants. Multiple stepwise regression was used to identify predictors of the NQEX-RPN. Results: Twenty-three courses and four clinical internships were positively associated with NQEX-RPN performance. Surgical nursing, Medical nursing, Computer basics and Community health care explained the 36.2% of the total variance of Theoretical Knowledge (F = 31.313, p = 0.000); clinical internships of obstetrics and gynecology nursing, pediatrics and surgical nursing explained the 28.1% of the total variance of Application Skills (F = 28.852, p = 0.000). Conclusion: Surgical-medicine nursing, Community health care, Computer basics and clinical internships are beneficial in assisting students and educators to identify the risk of students' performance in the NQEX-RPN.